2014
DOI: 10.3390/ijms150712217
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Intergeneric Conjugal Transfer System for Xinaomycins-Producing Streptomyces noursei Xinao-4

Abstract: To introduce DNA into Streptomyces noursei xinao-4, which produces xinaomycins, we explored an intergeneric conjugal transfer system. High efficiency of conjugation (8 × 10−3 exconjugants per recipient) was obtained when spores of S. noursei xinao-4 were heat-shocked at 50 °C for 10 min, mixed with Escherichia coli ET12567 (pUZ8002/pSET152) in the ratio of 1:100, plated on 2CMY medium containing 40 mmol/L MgCl2, and incubated at 30 °C for 22 h. With this protocol, the plasmids pKC1139 and pSET152 were successf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Restriction-modification system is an obstacle of introducing the plasmid into Gram-positive strains. The heat shock is usually applied to reduce the activity of a host restriction-modification system and to improve transformation efficiency [ 24 , 36 , 37 , 38 ]. To determine whether the heat shock would improve the electroporation efficiency, a water bath suitable for Gram-positive strains was performed after electroporation according to previous reports [ 11 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Restriction-modification system is an obstacle of introducing the plasmid into Gram-positive strains. The heat shock is usually applied to reduce the activity of a host restriction-modification system and to improve transformation efficiency [ 24 , 36 , 37 , 38 ]. To determine whether the heat shock would improve the electroporation efficiency, a water bath suitable for Gram-positive strains was performed after electroporation according to previous reports [ 11 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Theoretically, the described procedure provides a promising approach for the ultimate site-specific homologous recombination between this cassette and the bacterial chromosome to generate targeted gene knockouts. However, in practice, it does not work properly for every Streptomyces species, and further optimization is often required to successfully conjugate E. coli with refractory species (62)(63)(64)(65). Various species-dependent parameters which strongly affected the transformation efficiency were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Various species-dependent parameters which strongly affected the transformation efficiency were identified. Sun et al (64) found that the ratio of donor to recipient cell numbers was the most influential factor for conjugation into Streptomyces noursei. Also, for Streptomyces diastatochromogenes, the number of spores and their use instead of mycelia, in combination with a cultivation step at 30°C subsequent to the heat shock, were found to be the most important factors (65).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection of an appropriate conjugation medium has an obvious influence on the conjugation efficiency in streptomycetes (Du et al, 2012;Sun et al, 2014), so three applicable solid media, MS, TSB, and 2CMC, were tested to determine the appropriate medium. The 2CMC medium proved to be optimal for the intergeneric conjugation of E. coli-S. rimosus M527, whether mycelia or spores were chosen as recipient (Table 2).…”
Section: Development and Optimization Of Intergeneric Conjugation Tramentioning
confidence: 99%